Analisis potensi konflik akibat bahaya alam dan teknologi di RS Hermina Bekasi pasca PPKM - Kieso Koessaraffer; Ari Nurfikri (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Unanticipated emergencies can lead to disasters, whether caused by natural or human factors. Disasters result in loss of life, environmental damage, and economic impact. The Hazard Vulnerability Analysis (HVA) method assists hospitals in identifying potential hazards and vulnerabilities, both from natural hazards (such as earthquakes and floods) and technical failures (such as electrical outages). The objective of this study is to analyze the potential conflicts arising from natural and technological hazards at RS Hermina Bekasi after the end of PPKM. Methods: This research uses secondary data from HVA RS Hermina Bekasi and primary data through interviews with the hospital’s occupational health and safety (K3RS) team. The analysis is conducted using a qualitative method. Findings: Earthquakes have a risk percentage of 33%, making it the highest risk within the natural hazards category. The Regional Disaster Management Agency (BPBD) plays a crucial role in disaster response and management. Internal fires carry a risk percentage of 22%, the highest in the technological hazards category. The fire department's presence during fire incidents is to assist in extinguishing and mitigating the situation. Conclusion: RS Hermina Bekasi prioritizes earthquake and internal fire hazards, with disaster response plans, simulations, and collaboration to ensure emergency preparedness. Novelty/Originality of this article: This article reveals a comprehensive analysis of potential conflicts from natural and technological hazards in hospitals post-PPKM, highlighting preparedness priorities for earthquakes and internal fires.